TESL in-service teachers' experiences when evaluating an oral history workbook - Azlina Abdul Aziz,; Rosmizal Makhtar, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The implementation of the Common European Framework of Reference (CEFR) in English curriculum has led to the use of CEFR aligned foreign textbooks in Malaysian schools. However, the application of CEFR English textbooks from the United Kingdom has encountered a few oppositions as the advocates of Malaysian-based textbooks believe that English should be written contextually by emphasizing the local cultures and histories. In lieu of this, a group of in-service teachers in a Master’s course had developed and evaluated each other’s Oral History materials. The research objectives are to find out what are the material evaluation criteria frequently attended to by in-service TESL teachers when evaluating an oral history workbook and to what extent the inservice teachers have gained from evaluating oral history workbook developed by their peers. A mixed methodology research approach using basic frequency count, percentage value and qualitative data was employed in this study. Data was gathered from 109 in-service TESL teachers via their Personal Reflective Journal (PRJ), which they had written after evaluating an oral history workbook based on Tomlinson’s and Mukundan’s evaluation checklists. The findings identified the frequently attended criteria by the in-service teachers and that there are new criteria that can be added to the evaluation checklists. It is anticipated that this study could encourage educators to develop their own classroom materials, and material evaluators to consider the use of locally based English textbook and a revision to the material evaluation checklists to reflect current 21st century pedagogy.